Die frühen Inschriften Ägyptens eine Konkordanz der Nummerierungssysteme - Sperveslage, Gunnar (Golden House Publications, 2021)
The numbering system for the Early Egyptian inscriptions, which was originally introduced by J. Kahl (1994) and which was expanded by I. Regulski in her Database of Early Dynastic inscriptions, is mapped on the numbering system defined by J. Kahl, N. Kloth and U. Zimmermann (1995) for the 3rd Dynasty inscription and on this of P. Kaplony (IAEF, IAEFS, KBIAEF). The numbering system has been expended to provide a unique identifier for each inscription that can be used as a reference in databases and printed publications
Keywords: Inschrift; Nummerierung; Ägypten -- Altertum; Inscriptions, Egyptian; Konkordanz